ความสัมพันธ์ของดัชนีทางโภชนาการและการออกกำลังกายต่อความหนาแน่น มวลกระดูกในกลุ่มผู้หญิงไทยวัยหมดประจำเดือนซึ่งมีภาวะกระดูกบาง/กระดูกพรุน RELATIONSHIP OF NUTRITIONAL INDICES AND PHYSICAL ACTIVITY TO BONE MINERAL DENSITY IN OSTEOPENIA/OSTEOPOROSIS THAI POSTMENOPAUSAL WOMEN - วรรณะเอี่ยมพิกุล, ศิวพร; ตั้งตรงจิตร, รังสรรค์; ทองบุญชู, จุฑาภรณ์; อุเทนนาม, ดรุนี; สุทธิศันสนีย์, อุทัยวรรณ; สุทธิศันสนีย์, อุทัยวรรณ; อ่อนน้อม, ณัฐิรา; ชูพีรัชน์, เชาวนี (Srinakharinwirot University Journal of Sciences and Technology, 2021)
Osteoporosis associates with lifestyle factors. To identify the environmental factors both of the dietary and activity patterns associated with osteoporosis in Thai postmenopausal women. The study population was derived from the data during 2007 to 2014. This cross-sectional study was performed in 331 Thai postmenopausal female volunteers, who attended the menopause clinic post-operation follow up clinic, Department of Obstetrics and Gynecology, Ramathibodi Hospital, Bangkok, for a physical check-up and bone mineral scan by dual-energy x-ray absorptiometry (DEXA). The prevalence of Thai postmenopausal women in this study were osteopenia (46.5%) and osteoporosis (28.4%) (classified by T-score bone mineral density; BMD at any sites). After adjustment for age and BMI, the data from questionnaire were analyzed. Weight, height, BMI, exercise, protein-sourced food, and biochemical parameters including calcium and phosphorus levels were associated with BMDs. The public health care system should concern in osteoporosis situation. The lifestyle factors, especially dietary factor, are associated with bone mineral density (BMD). This research recommended that exercise and dietary are very important factors for reducing the risk of osteoporosis. Further investigations with quantitative analysis of food and nutrient consumption and long-term follow-up should be investigated.